FORECASTING OF PEACH AREA AND PRODUCTION WISE ECONOMETRIC - A. Ullah; D. Khan; S. Zheng (Journal of Animal and Plant Sciences, 2018)
The study was aimed at forecasting peach area and production in Pakistan using time series data for the period 1997-98 to 2014-15. Peach area and production were forecasted over a period of time 2015-2016 to 2025-26. The Box-Jenkins (1976) approach was applied to forecast area and production of peach. This study found ARIMA (1,1,0) as an appropriate model to forecast both area and production of peach. The best-forecasted model was determined based on the lowest values of Akaike information criterion, Bayesian information criterion and Hannan-Quinn criterion. However, the predictability power, performance and quality of the model was measured based on the lowest error value of the root mean square error, mean absolute error and mean absolute prediction error. The forecasted value of area and production of peach for the year 2025-26 were worked out as 11.05 thousand hectares and 65.05 thousand tonnes respectively. The minimum projection trend indicated declining area and production of peach in Pakistan. The author (s) may arrived at the conclusion that peach production can be increased by using improved peach cultivars, improved irrigation system and adequate cultural practices during the course of study in Pakistan. The strategy may be prioritized to bring more barren land under peach cultivation. Expansion of the area under peach would directly increase its production in the future. cultivation is declining day by day both in acreage and
Keywords: ARIMA; Box- Jenkins; Forecasting; Peach.